Optimization of Learning Effectiveness through the Learning Environment and Learning Motivation for Students - Masduki Ahmad (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to analyze the impact given by the learning environment and learning motivation on the student learning effectiveness at As-Syafiiyah Islamic University. This research is based on the problem that education in Indonesia is currently paralyzed, including higher education at universities, one of which is the As-Syafiiyah Islamic University. A quantitative methodology is a technique used in this study with the primary model of multiple linear regression. Using the Slovin formula, the research participants were 340 students from various study programs at the As-Syafiiyah Islamic University. Research data was obtained through a questionnaire distributed online. Statistical calculations were carried out using SPSS 25, and the hypothesis test used the t-test and f-test. It was revealed that: 1) the learning environment significantly and positively affects the learning effectiveness at As-Syafiiyah Islamic University; 2) the learning motivation significantly and positively affects the learning effectiveness at As-Syafiiyah Islamic University, and 3)both of learning environment and learning motivation impact student learning effectiveness at As-Syafiiyah Islamic University by 77.5%. This research is expected to have implications for improving the quality of education during the pandemic. In particular, it can illustrate how important the learning environment and learning motivation are to the university's effectiveness.